(3JTjjO GdbhGYO aj TQM JLQjO GdYbGFOs - (3TeS GdOjf eMehO Hf YHO GdQMef Hf CMeO GdCUagGfjs; (3GdfUjQ GdWhSj , eMeO Hf eMeO GdWhSj, fUjQ GdOjf CHh LYaQ,J (B672 (3g` s ((3Ydi Hf Ydi Hf CHj GdeLO s)
(3ChdgG (B:s
(3GdMeO ddg GdeJhMO HhLhH GdhLhO hOhGe GdHbGA GdeJaQO HGSJMGdI GdJZjjQ CeG HYO aEf CVYa HYGO Gddg hCMQLge Edi ZaQGfg GdCUagGfi s
(3BNQgG (B:s
(3ef CJi gPg GdbGPhQGJ adjSJQgG HSJQ Gddg gPG BNQ eG JjSQ dOjfG ef TQM GdJLQjO s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B30 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B207s
Keywords: (3GdJhMjO hGdedd hGdfMds